Identifying critical limits for soil quality indicators in agro-ecosystems - Arshad, M.A.; Martin, S. (Agriculture, ecosystems & environment, 2002)
The maintenance of soil quality is critical to environmental sustainability. Although, several papers have been published on this subject, progress in soil quality monitoring has been slow. Knowledge and assessment of changes (positive or negative) in its status with time is needed to evaluate the impact of different management practices. Selection of key indicators and their critical limits (threshold values), which must be maintained for normal functioning of the soil, are required to monitor changes and determine trends in improvement or deterioration in soil quality for various agro-ecological zones for use at district, national and global levels. Many soil indicators interact with each other, and thus, the value of one is affected by one or more of the selected parameters. Interdependence of pH and nutrient availability, electrical conductivity and infiltration, etc. has been well documented by many researchers. Some researchers have proposed procedures for evaluating soil quality functions by combining and integrating specific elements into soil quality indices. These procedures allow for weighting of various functions, depending upon the user goals and socio-economic concerns. Although, selection of soil indicators will vary with societal goals, the followings seem to be suitable indicators for crop production in most cases: organic matter, topsoil-depth, infiltration, aggregation, pH, electrical conductivity, suspected pollutants and soil respiration. Crop yield can be used as an integrator of the foregoing soil indicators. A minimum set of data on soil indicators must be identified to develop meaningful soil quality assessment. Also, monitoring soil indicators needs to set up sampling strategies allowing assessment of changes in soil quality which might be hidden by soil heterogeneity, by seasonal fluctuations or by analytical uncertainties. This paper describes the guidelines that can be followed to identify critical limits for the key indicators and the procedure for monitoring changes in soil quality trend.